MODEL INTERAKSI KUALITAS AUDIT: ANALISIS EKONOMETRIK PENGARUH TEKANAN KLIEN DAN DURASI PERIKATAN AUDIT (AUDIT TENURE) DENGAN UJI MODERASI INDEPENDENSI AUDITOR (STUDI EMPIRIS KAP MAKASSAR) - Andi Rafiyadi Eka Saputra; Haliah; Darmawati (Paulus Journal of Accounting (PJA), 2025)
Abstract: Audit Quality Interaction Model. This study analyzes the effect of client pressure and audit tenure on audit quality with auditor independence as a moderating variable in Public Accounting Firms (KAP) in Makassar. Using quantitative methods with surveys of 31 auditors from 12 KAPs, data were analyzed using Moderated Regression Analysis (MRA). Results show client pressure has a significant positive effect on audit quality, audit tenure has a significant negative effect, auditor independence moderates the relationship between client pressure and audit quality, but does not moderate the relationship between audit tenure and audit quality.